Submuscular plating vs. elastic stable intramedullary nailing for diaphyseal femur fractures in children: a systematic review and meta-analysis - Li, Donghui; Wang, Xiangyue; Lu, Jialing; Xue, Mingfeng (Frontiers in Pediatrics, 2023)
Objectives: This review evaluates the safety and efficacy of submuscular plating (SMP) versus elastic stable intramedullary nailing (ESIN) in the treatment of pediatric femur shaft fracture. Method: Studies comparing the efficacy and safety of SMP and ESIN in pediatric shaft fracture were retrieved from five databases (PubMed, Embase, Cochrane, OVID, and Web of Science) from inception to March 2023 using a systematic literature search strategy. A total of 13 outcome measures, such as perioperative parameters, clinical outcomes, and radiographic results, were included in the meta-analysis. Results: Eight eligible studies involving 491 patients were included in the narrative synthesis. There were no significant differences in baseline characteristics between the two groups. Meta-analysis showed reduced radiation time (RT), soft tissue irritation and angular deformation in the SMP group than in the ESIN group. However, the SMP group had greater estimated blood loss (EBL) than the ESIN group. The duration of surgery, length of hospital stay (LOS), implant removal, complications requiring surgery, Flynn score, incidence of infection, fracture healing time, and limb length discrepancy (LLD) were similar between the two groups. Only one study reported higher incidences of fracture nonunion or delayed healing in the ESIN group. Conclusion: SMP is an effective and safe intervention superior to ESIN in reducing soft tissue irritation, angular deformation and radiation time. Given the presence of potential bias and heterogeneity, surgeons should select the treatment that would provide the best outcomes for EBL, LOS, operation time, and bone nonunion or delayed healing based on their experience.